Oxytocin and Its Relationship to Body Composition, Bone Mineral Density, and Hip Geometry Across the Weight Spectrum - Schorr, Melanie; Marengi, Dean A; Pulumo, Reitumetse L; Yu, Elaine; Eddy, Kamryn T; Klibanski, Anne; Miller, Karen K; Lawson, Elizabeth A (The journal of clinical endocrinology and metabolism, 2017)
ContextOxytocin (OXT), an anorexigenic hypothalamic hormone anabolic to bone, may reflect energy availability. Basal serum OXT levels are lower in anorexia nervosa (AN, state of energy deficit) than healthy controls (HC) and negatively associated with spine bone mineral density (BMD). Reports are conflicting regarding OXT levels in overweight/obesity (OB, state of energy excess). Relationships between OXT and BMD in OB and hip geometry across the weight spectrum are unknown.ObjectiveTo determine whether overnight serum OXT levels are (1) elevated in OB and (2) associated with body composition, BMD, and hip geometry across the weight spectrum.DesignCross-sectional.SettingClinical research center.ParticipantsFifty-nine women, ages 18 to 45 years: amenorrheic AN (N = 16), eumenorrheic HC (N = 24), eumenorrheic OB (N = 19).Main Outcome MeasuresSerum sampled every 20 minutes from 8 pm to 8 am and pooled for integrated overnight OXT levels. Body composition, BMD, and hip structural analysis measured by dual x-ray absorptiometry.ResultsOXT levels were lowest in AN, higher in HC, and highest in OB (P ≤ 0.02). There were positive associations between OXT and (1) body mass index (P = 0.0004); (2) total, visceral, and subcutaneous fat (P ≤ 0.0002); (3) spine and hip BMD Z-scores (P ≤ 0.01); and (4) favorable hip geometry, namely buckling ratio (P ≤ 0.05). In a subset analysis of HC and OB, relationships between OXT and body composition, but not bone parameters, remained significant.ConclusionsThese data suggest OXT is a marker of energy availability and may be a mediator of bone density, structure, and strength. OXT pathways may provide targets for obesity and osteoporosis treatment.Oxytocin levels are elevated in women with obesity compared with normal-weight women, are a marker of energy availability, and may be a mediator of bone density and strength across the weight spectrum.